Pelaksanaan Asesmen Formatif dan Sumatif Kurikulum Merdeka di SD N Ngasinan - Mustamid; Fidya Aminah (Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research is motivated by fundamental changes due to the transition of the curriculum from the 2013 Curriculum to the Merdeka Curriculum, which causes teachers to find it difficult to adapt to building a complete understanding of formative and summative assessments. This study aims to determine the implementation of assessments and what are the supporting and inhibiting factors for the implementation of formative and summative assessments of the Merdeka Curriculum at SD N Ngasinan. This research uses a qualitative method with a case study design. The data collection techniques used are semi-structured interviews, observation, and documentation. The research subjects consisted of four parties, namely the principal, teachers (grades 1 and 4), 2 students, and curriculum management staff. The data analysis technique used Miles & Huberman which consists of data collection, data reduction, data presentation, and conclusion drawing. The results showed that assessment is carried out in accordance with the principles of assessment, but there are still shortcomings, namely formative assessment has not included self-assessment and peer assessment, summative assessment is limited to written test techniques and projects and teachers have difficulty applying the principle of fairness with the concept of differentiated learning. Supporting factors for the implementation of assessment at SD N Ngasinan are effective feedback, clear learning objectives, and active student participation. Meanwhile, the inhibiting factors are time constraints, large number of students, lack of teacher readiness and understanding, inaccuracy of instruments, and lack of student motivation. The strategies used are supervision by the principal, KKG and learning community, independent and formal training from the office and kapanewon, and freedom to participate in webinars and seminars.